Expanding the Spectrum of Alkali Retinopathy: Maculopathy following Alkali Burn - Andreas Vanclooster; Julie De Zaeytijd; Dimitri Roels (Case Reports in Ophthalmology, 2022)
Ocular alkali burns are known to cause profound damage to the anterior segment, especially the cornea and conjunctiva. However, rarely, additional adjacent chorioretinal complications may ensue. These chorioretinal complications appear primary by direct penetration of the alkali or secondary to an elevated intraocular pressure (IOP). In contrast to this, recent animal studies have suggested a causal link with upregulation of proinflammatory mediators. We present a patient with maculopathy following alkali ocular burn.